Intrinsic Capacity Deficits and 6-Month Outcomes in Older Adults with Acute LRTIs: A Multi-Center Study - Weng B; Jin J; Huang L; Jiao W; Wang M; Zhang X; Tong X; Li Y (Clinical Interventions in Aging)
Bingxuan Weng,1,2,* Jin Jin,1,* Lixue Huang,1 Wenshu Jiao,1 Mengyuan Wang,1 Xinyue Zhang,1 Xunliang Tong,1 Yanming Li1 1Department of Respiratory and Critical Care Medicine, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 2Peking University Fifth School of Clinical Medicine, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanming Li, Email lymly@263.netObjective: Intrinsic capacity (IC), representing an individual’s physical and mental abilities, is associated with adverse outcomes. Acute lower respiratory tract infections (LRTIs) contribute to poor long-term prognosis, yet effective assessment and intervention strategies remain limited. Given the critical role of IC in the aging population, understanding its prevalence and impact in older adults with LRTIs is crucial for improving management strategies. This study aims to characterize the domains and patterns of IC deficits and assess their influence on 6-month mortality and re-hospitalization in this population.Methods: This was a multi-center prospective cohort study conducted in China. Patients aged over 65 years hospitalized for acute LRTIs were consecutively enrolled and underwent IC evaluations upon admission between April 15, 2021, and January 15, 2023. Outcomes included 6-month mortality and re-hospitalization. Latent class analysis identified patterns of IC deficits, and multivariable logistic regression models assessed associations between IC deficit domains/patterns and adverse outcomes.Results: A total of 1,001 older patients were included, with a mean age of 76 years (IQR: 69– 84). Most of (839, 83.8%) the patients had at least one IC domain deficit. The 6-month re-hospitalization and mortality rates were 20.7% (190/933) and 7.7% (70/914). More domains of IC deficits, particularly in cognition (OR 1.873) and vitality (OR 1.737) deficits were associated with increased 6-month re-hospitalization rates. Three distinct IC deficit patterns were identified: relatively robust (73.5%), limited vitality and locomotion (18.6%), and impaired cognition, vision, and hearing group (7.9%). Compared to the relatively robust group, the limited vitality and locomotion group had a significantly higher risk of re-hospitalization (OR 2.025, 95% CI 1.388– 2.932).Conclusion: IC deficits were prevalent and associated with increased re-hospitalization in older adults with LRTIs. Early detection and targeted interventions may reduce re-hospitalization rates and improve patient outcomes.Keywords: ICOPE, intrinsic capacity, acute lower respiratory tract infections, older adults, long-term